Study of Topographical Properties of CuO thin film prepared by CBD method at various deposition times - Tahseen Ali Aswad (Tikrit Journal of Pure Science, 2021)
In this study, thin films of copper oxide (CuO) prepared using a chemical bath deposition (CBD) method on glass substrate. Aqueous copper sulfate (CuSo4.5H2O) used to obtain the required thin films and in concentration 0.1M. The films prepared during different deposition times (1, 4 and 8) days at room temperature. The XRD studies showed that the thin film prepared at deposition time (8 days) has polycrystalline structure (monoclinic structure). Morphological studies by using AFM measurements and topographical studies by using SEM measurements revealed that the surfaces of the prepared thin films show better uniformity when increasing deposition time from 1 day to 8 days, where the average diameter, roughness rate and root mean square (RMS) decreased with increasing deposition time